2020
DOI: 10.1002/acp.3632
|View full text |Cite
|
Sign up to set email alerts
|

Wandering eyes: Eye movements during mind wandering in video lectures

Abstract: Summary Video lectures are increasingly prevalent, but they present challenges to learners. Students' minds often wander, yet we know little about how mind wandering affects attention during video lectures. This paper presents two studies that examined eye movement patterns of mind wandering during video lectures. In the studies, mind wandering reports were collected by either self‐caught reports or thought probes. Results were similar across the studies: mind wandering was associated with an increased allocat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Over the past few years, an increasing number of studies have investigated the relationship between eye movements and MW (e.g., Faber et al, 2020;Frank et al, 2015;Krasich et al, 2018;Reichle et al, 2010;Steindorf & Rummel, 2020;Uzzaman & Joordens, 2011;Zhang et al, 2020), but so far little attention has been given to scanpaths. Moreover, the majority of those studies were concerned with reading comprehension, which involves quite different gaze control mechanisms (Castelhano & Rayner, 2008;Rayner et al, 2009).…”
Section: Mind-wandering and Eye Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, an increasing number of studies have investigated the relationship between eye movements and MW (e.g., Faber et al, 2020;Frank et al, 2015;Krasich et al, 2018;Reichle et al, 2010;Steindorf & Rummel, 2020;Uzzaman & Joordens, 2011;Zhang et al, 2020), but so far little attention has been given to scanpaths. Moreover, the majority of those studies were concerned with reading comprehension, which involves quite different gaze control mechanisms (Castelhano & Rayner, 2008;Rayner et al, 2009).…”
Section: Mind-wandering and Eye Movementsmentioning
confidence: 99%
“…2)(Zhang et al, 2020; exp. 1)(Zhang et al, 2020; exp. 2Participants and Thought Probes in Published Studies Examining Gaze Patterns of Mind−wandering Note: Pupillometry studies are excluded Figure A1 The Number of Participants and Thought Probes in Published Studies Examining Gaze Pat--values from 1000 one-sample t-tests examining the difference between empirical values and values derived from random fixation sequences against 0.…”
mentioning
confidence: 99%
“…However, these studies did not attempt to ascertain the MW that occurred in an actual learning environment. Therefore, recent researchers have used Eye Tribe, the commercialized eye tracking equipment, to detect MW when learners are watching a video lecture in order to identify the timing of the occurrence of MW in real-life situations such as video learning and have examined the features of the eye movements of participants during the MW period [1,10].…”
Section: Detecting Mw By Eye-trackingmentioning
confidence: 99%
“…Scholars are focusing on mind-wandering (MW), a kind of attentional lapse. Recent studies have demonstrated that MW is very prevalent when students watch videos [10]. Additionally, people's minds wandered frequently, no matter what they did.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the stimuli in Krasich et al (2018) contained a large number of human faces and other complex objects. If during MW, participants prefer to look at human faces over other stimuli (Zhang, Miller, Sun, & Cortina, 2020) and human faces happen to distribute widely across the scene, fixation dispersion may increase. Third, the stimulus presentation time (45 -75 sec) in Krasich et al (2018) was much longer compared to the current study (10 sec) and the increase in dispersion was only significant towards the end of presentation time.…”
Section: Recurrence Patternsmentioning
confidence: 99%